Prostasomes as interlocutor for zygotic epigenome health: role of prostasome secretome in maintenance of zygotic epigenome.: Prostasomes in zygotic epigenome health - RAJHANS, RAJIB; Kumar, Amit (Indian Journal of Dairy Science, 2023)
Prostasomes as transgenerational epigenetic toolbox has not been established, its role in transferring small RNA, lncRNA as paternal messages is yet to be explored. The present study was undertaken to establish role of prostasomes in modulating testicular and vaginal environmental cues such as protein and RNA messages through to zygote and thereby acting as interlocutor of paternal genome. The results from the study found out prostasomes fusion with spermatozoa takes place at the time of maturation and capacitation wherein it causes downregulation of ROS (Protein and mRNA) in terms of decreased NADPH and NOS activity significantly (p<0.01), it was also found to modulate mitochondrial membrane potential significantly (p<0.01). Prostasome supplementation lead to increased survival of spermatozoa in sp-TALP medium and was found to be superior to cryopreserved and fresh semen when used in routine in vitro fertilization (IVF) experiment. The study further envisages to establish prostasomes as repository of novel biomarkers for infertility in male and female and as diagnostic tool in in vitro fertilization and somatic cell nuclear transfer protocol and thereby establishing prostasomes as one of the fundamental vesicles influencing transgenerational transfer of RNA and protein to zygotic genome thereby influencing zygotic genome health.